The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3109/01480545.2012.658403
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consumption of aspartame and brain antioxidant defense status

Abstract: The present study investigated the effect of long-term intake of aspartame, a widely used artificial sweetener, on antioxidant defense status in the rat brain. Male Wistar rats weighing 150-175 g were randomly divided into three groups as follows: The first group was given aspartame at a dose of 500 mg/kg body weight (b.w.); the second group was given aspartame at dose of 1,000 mg/kg b.w., respectively, in a total volume of 3 mL of water; and the control rats received 3 mL of distilled water. Oral intubations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…The present results propose that ASP (excitotoxic food additives) or its metabolites increase the permeability of BBB and can bypass the blood barrier system and enter the brain in toxic concentrations that produced brain lesions. In accordance with the present results, previous study of the neurotoxic action of ASP on neuronal brain structures, the chronic administration demonstrates the high vulnerability of brain structure and functionality to ASP or to its metabolites' toxicity (Iyyaswamy and Rathinasamy, 2012) and the exposure of brain rats to ASP results in the rapid depletion of cortical GSH followed by an increase in ROS and with a diminishing supply of GSH, there is an accumulation of excessive amounts of ROS and ultimately cell death, (Abhilash et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present results propose that ASP (excitotoxic food additives) or its metabolites increase the permeability of BBB and can bypass the blood barrier system and enter the brain in toxic concentrations that produced brain lesions. In accordance with the present results, previous study of the neurotoxic action of ASP on neuronal brain structures, the chronic administration demonstrates the high vulnerability of brain structure and functionality to ASP or to its metabolites' toxicity (Iyyaswamy and Rathinasamy, 2012) and the exposure of brain rats to ASP results in the rapid depletion of cortical GSH followed by an increase in ROS and with a diminishing supply of GSH, there is an accumulation of excessive amounts of ROS and ultimately cell death, (Abhilash et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…ASP is metabolized into three toxic molecules, phenylalanine (50%), aspartic acid (40%), and methanol (10%), which are then absorbed into the circulation and various neurochemical effects of ASP have been associated with increases in and persistence of their metabolites in CNS; those levels are controlled by the blood-brain barrier (BBB) (Humphries et al, 2008). ASP may also be carcinogenic because at least its metabolite diketopiperazine (DKP) can cause cancers in the central nervous system such as glioblastoma, medulloblastomas and meningiomas (Abhilash et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspartame is an artificial, non-saccharide sweetener and is considered to be closely linked with increased incidence of malignancy of brain tumors. It is suggested that long term use of aspartame might lead to improper antioxidant status of brain mainly through glutathionedependent system involvement [8].…”
Section: Introductionmentioning
confidence: 99%
“…Abhilash et al (2013) showed the effects of chronic aspartame ingestion in Wistar rats which resulted in imbalance in the oxidative states in the brain of the exposed, through a glutathionedependent system. In spite of controversial results for mutagenic and genotoxic profile in different study models, Yılmaz and Uçar (2014) in a revision highlight the genotoxic effects of aspartame, characterizing it as a moderate carcinogenic agent for humans, with positive results for 45% of the epidemiological studies.…”
Section: Biosci Jmentioning
confidence: 99%